UKPDS Outcomes Model 2: A new version of a model to simulate lifetime health outcomes of patients with type 2 diabetes mellitus using data from the 30 year united kingdom prospective diabetes Study: UKPDS 82 - Hayes, A; Leal, J; Gray, A; Holman, R; Clarke, P (2013)
Aims/hypothesis: The aim of this project was to build a new version of the United Kingdom Prospective Diabetes Study (UKPDS) Outcomes Model (UKPDS-OM1), a patient-level simulation tool for predicting lifetime health outcomes of people with type 2 diabetes mellitus. Methods: Data from 5,102 UKPDS patients from the 20 year trial and the 4,031 survivors entering the 10 year post-trial monitoring period were used to derive parametric proportional hazards models predicting absolute risk of diabetes complications and death. We re-estimated the seven original event equations and estimated new equations for diabetic ulcer and some second events. The additional data permitted inclusion of new risk factor predictors such as estimated GFR. We also developed four new equations for all-cause mortality. Internal validation of model predictions of cumulative incidence of all events and death was carried out and a contemporary patient-level dataset was used to compare 10 year predictions from the original and the new models. Results: Model equations were based on a median 17.6 years of follow-up and up to 89,760 patient-years of data, providing double the number of events, greater precision and a larger number of significant covariates. The new model, UKPDS-OM2, is internally valid over 25 years and predicts event rates for complications, which are lower than those from the existing model. Conclusions/interpretation: The new UKPDS-OM2 has significant advantages over the existing model, as it captures more outcomes, is based on longer follow-up data, and more comprehensively captures the progression of diabetes. Its use will permit detailed and reliable lifetime simulations of key health outcomes in people with type 2 diabetes mellitus. © 2013 Springer-Verlag Berlin Heidelberg.